Yksityisen kulutuksen ennustemalleja; Forecast Models for Private Consumption - Aleksandr Peussa (The Research Institute of the Finnish Economy (ETLA), 2014)
– The share of private consumption in gross domestic product is significant; therefore, private consumption has a great influence on economic growth, which makes it a major concept in economics. The purpose of the paper is to estimate and evaluate different forecasting models for private consumption. The first part of the paper focuses on the aggregate consumption. The models are estimated using yearly and quarterly data. The goal of second part of the paper is to estimate and evaluate forecasting models for the components of private consumption. Private consumption can be divided by the duration principle or by product categories. There are three competing statistical models for components of private consumption. All models are presented in the second part of the report and the aim is to choose the best model using statistical methods of model evaluation (R-squared, AIC, BIC).
Keywords: C43; C52; C53; E21; E27; C82; 330; Aggregate consumption; Private consumption; Economic forecasts; Logistic regression; Privater Konsum; Prognoseverfahren; Regressionsanalyse; Finnland